Pertumbuhan Bibit Tanaman Jarak Pagar (Jatropha curcas L.) pada Berbagai Kedalaman dan Posisi Tanam Benih - Santoso, Bambang B.; Purwoko, Bambang S. (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2008)
Germination and growth at seedling stage are critical phases in plant life cycle, especially for physic nut (Jatropha curcas L.) usually grown in a dry land. Therefore seedling preparation plays an important role in nursery stock production. Position and depth of seed sowing affected the germination process and further seedling growth and development. A Completely Randomized Design with two factors was used in the experiment, i.e., depth of seed sowing (1, 2, 3, 4, and 5 cm) and seed position (seed with micropyle at the bottom, face-down, and layback). The result showed that position and depth of seed sowing affected the germination and early growth and development of seedling. The effect of seed position on growth and development of seedling persisted until the end of the experiment when the seedlings were two months old. Face-down position with 2 - 3 cm depth represented the best position and depth for seedling growth. Key words: Early seedling growth, micropyle, face-down position, layback position